III-V semiconductor waveguides for photonic functionality at 780 nm - Maclean, Jessica O.; Greenaway, Mark T.; Campion, Richard P.; Pyragius, Tadas; Fromhold, T. Mark; Kent, Anthony J.; Mellor, Christopher J. (SPIE, 2014)
Photonic integrated circuits based on III-V semiconductor polarization-maintaining waveguides were designed and fabricated for the first time for application in a compact cold-atom gravimeter1,2 at an operational wavelength of 780 nm. Compared with optical fiber-based components, semiconductor waveguides achieve very compact guiding of optical signals for both passive functions, such as splitting and recombining, and for active functions, such as switching or modulation. Quantum sensors, which have enhanced sensitivity to a physical parameter as a result of their quantum nature, can be made from quantum gases of ultra-cold atoms. A cloud of ultra-cold atoms may start to exhibit quantum-mechanical properties when it is trapped and cooled using laser cooling in a magneto-optical trap, to reach milli-Kelvin temperatures. The work presented here focuses on the design and fabrication of optical devices for a quantum sensor to measure the acceleration of gravity precisely and accurately. In this case the cloud of ultra-cold atoms consists of rubidium (87Rb) atoms and the sensor exploits the hyperfine structure of the D1 transition, from an outer electronic state of 5 2S ½ to 5 2P3/2 which has an energy of 1.589 eV or 780.241 nm. The short wavelength of operation of the devices dictated stringent requirements on the Molecular Beam Epitaxy (MBE) and device fabrication in terms of anisotropy and smoothness of plasma etch processes, cross-wafer uniformities and alignment tolerances. Initial measurements of the optical loss of the polarization-maintaining waveguide, assuming Fresnel reflection losses only at the facets, suggested a loss of 8 dB cm-1, a loss coefficient, α, of 1.9 (±0.3) cm-1.